2011
DOI: 10.2527/jas.2010-3787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of source and quantity of dietary vitamin D in maternal and creep diets on bone metabolism and growth in piglets1

Abstract: Piglets are born with reduced plasma concentrations of 25-hydroxycholecalciferol (25-OH-D(3)) and are thus highly predisposed to vitamin D deficiency. Furthermore, sow milk contains little vitamin D, and the slow intestinal vitamin D absorption of sows limits the efficacy of dietary vitamin D supplementation. Hence, the neonate depends, to a large extent, on the vitamin D stores built up in fetal tissues from maternal sources. The current study was undertaken to evaluate whether the source and quantity of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 36 publications
4
40
1
Order By: Relevance
“…Previous reports from Coffey et al (2012) and Witschi et al (2011) (Haddad et al, 1971). The current data agree with previous reports and are the first to show a maternal dietary vitamin D 3 supplementation rate that provided a larger serum 25(OH)D 3 response in piglets compared with piglets from sows supplemented 50 μg of 25(OH)D 3 .…”
Section: (Oh)dsupporting
confidence: 82%
“…Previous reports from Coffey et al (2012) and Witschi et al (2011) (Haddad et al, 1971). The current data agree with previous reports and are the first to show a maternal dietary vitamin D 3 supplementation rate that provided a larger serum 25(OH)D 3 response in piglets compared with piglets from sows supplemented 50 μg of 25(OH)D 3 .…”
Section: (Oh)dsupporting
confidence: 82%
“…The maternal and nursery vitamin D treatment impacts on growing pig serum 25(OH)D 3 in this study were largely expected. Most previous reports (Lauridsen et al, 2010;Witschi et al, 2011;Coffey et al, 2012;Weber et al, 2014) have all shown that supplementation of 25(OH)D 3 at the same IU equivalency of vitamin D 3 will result in an increased serum 25(OH) D 3 response. Also, increasing maternal vitamin D 3 supplementation has been shown to lead to an increase in subsequent pig serum 25(OH)D 3 (Flohr et al, 2014a), which is consistent with results from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have been conducted to investigate vitamin D requirements and/or supplementation/administration to sows and piglets (Lauridsen et al, 2010; Witschi et al, 2011; Rortvedt et al, 2012; Flohr et al, 2014a). The supplementation of vitamin D to gestation and lactation diets at concentrations above NRC (1998) requirement was demonstrated to increase serum vitamin D concentration of sows (Lauridsen et al, 2010) and their progeny (Witschi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of vitamin D to gestation and lactation diets at concentrations above NRC (1998) requirement was demonstrated to increase serum vitamin D concentration of sows (Lauridsen et al, 2010) and their progeny (Witschi et al, 2011). Regarding vitamin D supplementation to piglets, when newborn pigs were supplemented with vitamin D 3 via oral administration at 40,000 or 80,000 IU of vitamin D 3 , higher serum 25-hydroxycholecalciferol (25-OH D 3 ) concentration was detected at weaning compared with pigs without vitamin D 3 administration (Flohr et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%